The Influence of The Family Environment on The Learning Outcomes of Generation Z at SMA Negeri 1 Wuryantoro - Purbo Laras, Sherina; Nawangtoro, Septa (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study investigates the influence of the family environment on the learning outcomes of Generation Z students at SMA Negeri 1 Wuryantorο, Indonesia. The research was motivated by increasing concern over how family conditions shape student learning in the digital era, particularly for adolescents who are highly exposed to technology. A quantitative explanatory survey design was employed, involving 106 Grade XI students selected through simple random sampling. Data were collected using validated and reliable self-administered questionnaires measuring family environment and perceived learning outcomes across cognitive, affective, and psychomotor domains. Statistical analyses included descriptive statistics, Pearson correlation, and simple linear regression, following confirmation of validity, reliability, and normality assumptions. The results reveal a strong and significant positive relationship between the family environment and learning outcomes, with a correlation coefficient of 0.698. Regression analysis indicates that the family environment explains 48.7% of the variance in students’ learning outcomes, demonstrating its substantial predictive power. These findings highlight that supportive family conditions remain a critical determinant of academic achievement for Generation Z students, despite the growing dominance of digital learning contexts. The study has important implications for educational practice and policy, emphasizing the need to strengthen school–family partnerships and family-centered educational interventions to reduce achievement disparities. Limitations include the single-school context and reliance on self-reported learning outcomes. Future research is recommended to involve broader samples, objective academic measures, and longitudinal or mixed-methods designs to deepen understanding of family influences on student learning.